The influence of propylene glycol on body condition and milk yield of cows as well as colostrum and milk composition - Robert Kupczyński; Maciej Adamski; Gustav Chládek (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2005)
The research was executed on 24 high yield dairy cows divided into three groups (n = 8). There was the control group (I) that the propylene glycol wasn’t given to cows, group II – the cows received 250 ml/day/per head of the propylene glycol, and the group III ─ the cows received 500 ml/day per head of the propylene glycol. The preparation was administered to cows per os beginning from 2 weeks before parturition to the end of the third week of lactation. During the research the condition of animals was estimated by BCS method, the daily yield was recorded, and analyses of the milk and colostrum composition were performed. The propylene glycol lightened the decrease of cows’ condition during entering at the peak of lactation. The higher dose (500  ml) was more profitable, because it had an influence on the content of the colostrum components, low urea level in milk as well as on daily yield, which was higher of about 3.64  kg while the preparation was given, in comparison to the control group. In the 3rd week of lactation the low level of somatic cells in milk of cows that received the preparation was stated. In conclusion, our study revealed a great positive effect of propylene glycol given to the cows shortly before and after parturition on their body condition and a less significant effect on colostrum quality and milk yield.